Addressing Surgical Care Disparities: Residents' Involvement in Global Mission Trips. Issue 2 (14th March 2022) - Kambhampati, Praneeth V.; Mitchell, David; Rajesh, Aashish; Deptula, Peter L.; Asaad, Malke
Abstract : Abstract: Humanitarian mission trips have been organized by several residency programs and organizations to cater to surgical care in underdeveloped countries. While there is cross-talk on the existence of such opportunities, there is a paucity of guidance to residents on participation in such trips, their benefits, and the myriad of intangibles to consider while planning to pursue such opportunities. Through this article, the authors highlight the background and utility of humanitarian surgical missions and summarize the clinical and surgical experiences that these trips offer for residents choosing to embark on these altruistic journeys.